Літературознавство про становлення російського історичного роману (до ХХ ст.) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
Taking into consideration the data fixed in the literary field, the article highlights the main stages of developing the Russian historic novel in the XIX-th century. It deals with the historic novels by Zagoskin, Bulgarin, Polevoy, Laзhechnikov, Gogol, Pushkin, Tolstoy. All these novels prove the fact of the genesis of the genre in question in Russia.